2012
DOI: 10.1155/2012/767582
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Root Canal Configuration of Maxillary Second Molar: A Case Report

Abstract: A thorough knowledge of root canal morphology is a prerequisite for the endodontic therapy. The maxillary molars, especially the second molars, have the most complicated root canal system in permanent dentition. There are many variations in canal number and configuration in maxillary molars. Treatment may be unsuccessful because the dentist may fail to recognize the unusual canal configuration. The present paper describes a case of a right maxillary second molar with a canal configuration rarely reported in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The permanent first maxillary molar (1MM) and permanent second maxillary molar (2MM) are the teeth that present the greatest complexity and variation in the root canal system [1, 2], and this is reflected in them having the highest rates of endodontic failure and being a constant challenge for the clinician [3]. …”
Section: Introductionmentioning
confidence: 99%
“…The permanent first maxillary molar (1MM) and permanent second maxillary molar (2MM) are the teeth that present the greatest complexity and variation in the root canal system [1, 2], and this is reflected in them having the highest rates of endodontic failure and being a constant challenge for the clinician [3]. …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, it can be concluded that the incidence of the second canal (MB2) inthe mesial root is higher than 50%. Other variations that have been reported in this type of tooth group include the presence of a third canal in the mesial root [ 8 ], a second canal in the palatal root [ 9 ], and two individual palatal roots (mesiopalatal and distopalatal) with their own separate canals [ 10 ]. Moreover, C-shaped configuration [ 11 ] has also been reported, as well as root fusion of two or more roots [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies demonstrated that mesiobuccal (MB) root canal system is not simple, but include very fine and complex structures, such as accessory canals, inter-canal communications, apical fins, deltas, and ramifications 4-6. Because of the importance of knowledge on these micro-structures, there have been numerous studies which investigated the maxillary molar MB root canal morphology by in vivo and laboratory methods 7-11.…”
Section: Introductionmentioning
confidence: 99%